Some observations on the greatest prime factor of an integer - Jakimczuk, Rafael (Annales Mathematicae Silesianae, 2022)
We examine the multiplicity of the greatest prime factor in k-full numbers and k-free numbers. We generalize a well-known result on greatest prime factors and obtain formulas related with the Riemann zeta function.